Structural and visible-near infrared optical properties of sodium tungsten bronze particles synthesized by one-step ball milling method - Noinonmueng, Tanisara; Kansaard, Thanaphon; Pinthong, Phonlawee; Moonseeda, Watcharakorn; Songpanit, Maneerat; Mekprasart, Wanichaya; Boonyarattanakalin, Kanokthip; Jayasankar, C. K.; Pecharapa, Wisanu (My University, 2025)
Near Infrared (NIR) shielding is a challenging issue in developing novel technology for smart building applications. Tungsten bronze-based material is one of the interesting materials for IR absorption and shielding applications. This research work aims to conduct the facile synthesis of sodium tungsten bronze powder (NaxWO3) via a high energy ball milling technique. The effect of ball milling time on the properties of the prepared product was investigated by relevant characterization techniques including X-ray diffraction technique, electron microscopy, X-ray photoelectron spectroscopy, and UV–vis–NIR spectrophotometry. At certain milling of 2–3 h, the corresponding results exhibited the phase transformation from starting precursor to the Na0·3WO3 phase with good near-infrared absorptivity due to localized surface plasmon resonance phenomena of this phase.
Keywords: Ball milling process; Near infrared shielding; Sodium tungsten bronze